2015
DOI: 10.1016/j.renene.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variability of ground thermal properties in glacial sediments and implications for horizontal ground heat exchanger design

Abstract: 9Thorough characterization of the spatiotemporal variability in soil thermal properties can 10 facilitate better designs for horizontal geothermal heat pump (HGHP) systems by reducing ground heat 11 exchanger (GHEX) costs. Results are presented from a new monitoring network installed across a range 12 of glaciated terrains in Indiana (USA), including the first known observations of the dynamic range of 13 thermal conductivity that occurs at the depth of horizontal GHEX installations. In situ thermal 14 conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…This is done by comparing the spectral data registered by the instrument (Rietveld, 1969;Hillier, 2000); -thermal conductivity by thermal properties analyser (KD2Pro apparatus, Decagon Devices, Inc.). The device consists of a handheld controller and a single needle sensor probe (TR-1, 2.4 mm diameter, 10 cm long needle) operating according to the transient line source method (ASTM D5334-08, Naylor et al, 2015); -moisture content by time-domain reflectometry (TDR) device (TRIME IMKO GmBH). The device allows the determination of the soil moisture content (probe range 0-100%), empirically related to the apparent dielectric constant (ka) of the soil (IMKO Micromodultechnik GmbH; Susha Lekshmi et al, 2014); -bulk density as determined on a duly collected sample (for every moisture content step and load) according to the DIN 52102-2; -water content as determined on a duly collected sample (for every moisture content step and load) according to the DIN 18121-1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is done by comparing the spectral data registered by the instrument (Rietveld, 1969;Hillier, 2000); -thermal conductivity by thermal properties analyser (KD2Pro apparatus, Decagon Devices, Inc.). The device consists of a handheld controller and a single needle sensor probe (TR-1, 2.4 mm diameter, 10 cm long needle) operating according to the transient line source method (ASTM D5334-08, Naylor et al, 2015); -moisture content by time-domain reflectometry (TDR) device (TRIME IMKO GmBH). The device allows the determination of the soil moisture content (probe range 0-100%), empirically related to the apparent dielectric constant (ka) of the soil (IMKO Micromodultechnik GmbH; Susha Lekshmi et al, 2014); -bulk density as determined on a duly collected sample (for every moisture content step and load) according to the DIN 52102-2; -water content as determined on a duly collected sample (for every moisture content step and load) according to the DIN 18121-1.…”
Section: Methodsmentioning
confidence: 99%
“…The change of values is more pronounced in coarse-grained than in clay and silty dominated sediments. This indicates that well-graded soils can retain a greater amount of water, a very important condition if improved thermal conductivities are desired over time (Di Sipio et al, 2016;Naylor et al, 2015;Usowicz et al, 1996;Smits et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, these types of exchangers are more sensitive to atmospheric fluctuations and to soil moisture dynamics because they are buried at shallow depths. Naylor et al [6] and Wu et al [7] evaluated how site-specific soil properties impact horizontal ground source heat pump (GSHP) systems designed for residential-scale installations. They calculated GHE loop lengths following the International Ground Source Heat Pump Association recommended practice and by using a standard method for estimating soil thermal properties based on simple soil classification obtained from published soil maps.…”
Section: Introductionmentioning
confidence: 99%
“…Ground thermophysical properties including soil texture, grain size distribution, bulk density, water content and thermal conductivity are correlated and highly influences the heat transfer between the circulating HTF in the GHEs and the surrounding soil, affecting the performance of the system (Bertermann et al 2015;Luo et al 2016;Kim et al 2016;Kavanaugh 2000). HGHEs are preferred over VGHEs for residential installations because of their lower initial installation costs (Naylor et al 2015). Although HGHEs offer a costeffective and environmentally friendly alternative compared to other methods, large shallow land areas are required for pipe installations and the system is affected by temperature fluctuations caused by the system's proximity to the ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental, numerical, economic and performance prediction studies related to GHEs have been reported in literature. The studies can be categorised into three broad groups: (i) Solar collectors coupled with a GSHP system (Yamankaradeniz & Horuz 1998;Huang & Chyng 2001;Kaygusuz 2000;Reyes et al 1998;Ball et al 1983); (ii) Ground heat exchanger systems coupled with a GSHP (Gan et al 2007;Kim et al 2016;Luo et al 2016;Bertermann et al 2015;İnallı & Esen 2004;Esen et al 2016;Cui et al 2008;Florides & Kalogirou 2007;Naylor et al 2015;Ball et al 1983) (iii) Solar collectors coupled with a GHEs and a GSHP for heating purposes (İnallı & Esen 2004;Ozgener & Hepbasli 2005a;Ozgener & Hepbasli 2005b;Inalli & Esen 2005;Verma & Murugesan 2014;Badescu 2002;Esen et al 2016). Bose & Smith (1992) developed the first solar GHE, coupled with a GSHP at Oklahoma State University.…”
Section: Introductionmentioning
confidence: 99%